(untitled) (International Journal of Food and Nutritional Sciences, 2022)
This article presents a comprehensive study conducted to explore the innovative skills of principals in arts and science colleges in Kerala. The research addresses the existing research gap in understanding the specific innovative skills required by principals in these institutions. The objectives, scope, significance, methodology, hypothesis, data analysis, findings, conclusions, and suggestions are discussed in detail. The findings provide valuable insights for enhancing the innovative skills of principals and promoting excellence in educational leadership in Kerala’s arts and science colleges.